Health Behavior and Emotional Responses of Thai National Team Athletes during the COVID-19 Pandemic: A Comparative Study of Individual and Team Sports - Pluemsamran, Theeratheeta; Pariyavuth, Pariya; Pochai, Nopparat; Panurushthanon, Phichayavee; Punthipayanon, Sirichet (My University, 2025)
Objectives: COVID-19 significantly impacted athletes’ health behavior and emotional well-being. Disruptions to training routines, competition schedules, and social structures raised concerns about psychological resilience, especially for elite athletes. In this study, we (1) adapted and validated the Emotional State Questionnaire (EST-Q-2) for Thai athletes, (2) examined the emotional responses and associated health behavior patterns of Thai national team athletes during the COVID-19 pandemic, and (3) compared emotional states between individual and team sport athletes. Methods: We surveyed 280 Thai national team athletes (146 male, 134 female) preparing for the 19th Asian Games. Participants completed the culturally adapted EST-Q-2, measuring 5 dimensions: depression, general anxiety, panic disorder, fatigue, and insomnia. We compared emotional responses by sport type. Results: The most prominent symptoms reported were fatigue and insomnia (M = 3.26), general anxiety (M = 2.84), depression (M = 2.35), and panic disorder (M = 2.17). We found no statistically significant differences between individual and team sport athletes across emotional dimensions. The adapted EST-Q-2 demonstrated strong reliability (Cronbach’s α = 0.80). Conclusion: The COVID-19 pandemic adversely affected the emotional states and health behavior of Thai national athletes, with high levels of fatigue and sleep disturbances. The lack of significant differences between sport types indicates a universal psychological impact, underscoring the need for targeted mental health interventions regardless of sport category.
Keywords: Athlete Mental Health; COVID-19; Emotional States; Health Behavior; Individual Sports; Team Sports